2021
DOI: 10.1177/03000605211015023
|View full text |Cite
|
Sign up to set email alerts
|

Development and external validation of a nomogram predicting overall survival after curative resection of colon cancer

Abstract: Objective To develop and externally validate a prognostic nomogram to predict overall survival (OS) in patients with resectable colon cancer. Methods Data for 50,996 patients diagnosed with non-metastatic colon cancer were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database. Patients were assigned randomly to the training set (n = 34,168) or validation set (n = 16,828). Independent prognostic factors were identified by multivariate Cox proportional hazards regression analysis and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…These ndings are consistent with previous studies that have been done in the eld of predicting the survival of patients after surgery in colon cancer (16-18). For instance, Wang et al (2021) developed a nomogram to predict the overall survival of patients after curative surgery for colon cancer, which showed that age, tumor size, differentiation, TNM stage, and chemotherapy were independent predictors of overall survival (18).…”
Section: Discussionmentioning
confidence: 99%
“…These ndings are consistent with previous studies that have been done in the eld of predicting the survival of patients after surgery in colon cancer (16-18). For instance, Wang et al (2021) developed a nomogram to predict the overall survival of patients after curative surgery for colon cancer, which showed that age, tumor size, differentiation, TNM stage, and chemotherapy were independent predictors of overall survival (18).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that through using the model developed in the present study, surgeons could better assess the risk of individual postoperative complications and may match interventions for patients who need more intensive treatment. To the best of our knowledge, our study is the first to specifically concentrate on a nomogram for predicting postoperative complications after emergency surgery for colon cancer, which is unlike the current nomograms for colon cancer that mainly focus on the evaluation of the overall survival prognosis, from an oncological point of view [ 40 ], or focus on the prediction of anastomosis fistula after colic resections [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, it ignores some factors that have been proved to be of prognostic value, which results in the prediction system having certain limitations. Therefore, some studies based on Cox proportional hazards regression have improved the accuracy of the clinical prognostic model by including more predictors ( 2 ) or adjusting the weight ( 3 ) of predictors in TNM stage. However, some studies have found that the models built using these linear methods ignore the time-dependent and nonlinear effects between CRC predictors and prognosis ( 4 ), which may cause the phenomenon of “survival paradox”, and result in clinicians being unable to accurately evaluate the prognosis of CRC patients ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%